2016
DOI: 10.4049/jimmunol.1501582
|View full text |Cite
|
Sign up to set email alerts
|

GIMAP1 Is Essential for the Survival of Naive and Activated B Cells In Vivo

Abstract: An effective immune system depends upon regulation of lymphocyte function and homeostasis. In recent years members of the GTPases of the Immune Associated Protein (GIMAP) family have been proposed to regulate T cell homeostasis. In contrast, little is known about their function and mode of action in B cells. We have used a combination of transgenic mice and in vivo and in vitro techniques to conditionally and electively ablate GIMAP1 in resting and activated peripheral B cells. Our data suggest that GIMAP1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 62 publications
1
18
0
1
Order By: Relevance
“…This finding may explain the lack of autoimmunity observed in the Gimap1 f/f CD2Cre + strain of mice and suggests that, despite their structural similarities, GIMAP1 and GIMAP5 perform discrete functions in T cells. In recent work we have looked at the effect of GIMAP1 deletion in B cells and also find that both resting and activated B cells depend on GIMAP1 for their survival . Interestingly, attrition in the T‐cell compartments of GIMAP5‐deficient mice is aggravated as the animals age .…”
Section: Discussionmentioning
confidence: 99%
“…This finding may explain the lack of autoimmunity observed in the Gimap1 f/f CD2Cre + strain of mice and suggests that, despite their structural similarities, GIMAP1 and GIMAP5 perform discrete functions in T cells. In recent work we have looked at the effect of GIMAP1 deletion in B cells and also find that both resting and activated B cells depend on GIMAP1 for their survival . Interestingly, attrition in the T‐cell compartments of GIMAP5‐deficient mice is aggravated as the animals age .…”
Section: Discussionmentioning
confidence: 99%
“…Slamf 7 regulates differentiation of various lymphocyte lineages. Gimaps are essential for survival of naïve and activated B-and T-cells 44,45 . Several genes indicated higher activity of B-cells in H-gEBV.…”
Section: Differential Gene Expression 4 Weeks Post-challenge Many Immentioning
confidence: 99%
“…GIMAPs are involved in the development, maintenance, and homeostasis of lymphocytes, especially CD4 + T cells and B cells, but also T regulatory cells (Tregs) (53)(54)(55). In the absence of individual GIMAP members, there is progressive lymphocyte loss leading to lymphopenia, poor cell proliferation, and paradoxical autoimmune states because of impaired Treg function (54)(55)(56)(57)(58). A previous gene family analysis showed that the GIMAP family is expanded in the Egyptian rousette compared to a bat ancestor (19), with 14 putative members.…”
Section: Discussionmentioning
confidence: 99%